Supplemental Blue Light Frequencies Improve Ripening and Nutritional Qualities of Tomato Fruits - He, Rui; Wei, Jingjing; Zhang, Jiye; Tan, Xin; Li, Yamin; Gao, Meifang; Liu, Houcheng (Frontiers in Plant Science, 2022)
Tomatoes (Solanum lycopersicum L. Micro-Tom) were grown under plastic greenhouse. When plants anthesis, the 100 μmol‧m–2‧s–1 blue LED light (430±10 nm) was supplemented from 6:00 to 18:00. There were 5 treatments which contained different blue light frequencies with the same intensity: S6 (30 min blue light and 30 min pause), S8 (30 min blue light and 15 min pause), S10 (30 min blue and 8 min pause), S12 (continuous blue light for 12h), and control (CK, natural light). Agronomic traits and nutritional qualities of tomato fruits were measured at 30, 34, 38, 42 and 46 days after anthesis (DAA), respectively. Different frequencies of supplemental blue light could accelerate flowering of tomato plants and promote fruit ripening about 3 to 4 days early via promoting ethylene evolution of fruits, which significantly facilitated the processes of color change and maturity in tomato fruits. The contents of lycopene, total phenolic compounds, total flavonoids, vitamin C and soluble sugar, as well as the overall antioxidant activity of tomato fruits were significantly enhanced by all supplemental blue light treatments. In all, different frequencies of supplemental blue light prominently reinforced the antioxidant levels and nutritional qualities of tomato fruits, especially lycopene content, and S10 was more optimal for tomato fruits production in plastic greenhouse.